2020
DOI: 10.1245/s10434-020-08758-2
|View full text |Cite
|
Sign up to set email alerts
|

The MelFo Study UK: Effects of a Reduced-Frequency, Stage-Adjusted Follow-Up Schedule for Cutaneous Melanoma 1B to 2C Patients After 3-Years

Abstract: Background Evidence-based guidelines for follow-up treatment of American Joint Committee on Cancer (AJCC) stages 1B to 2C melanoma patients are lacking. The MELanoma FOllow-up study is an international phase 3 randomized trial, and the 3-year interim data were recently reported from the Netherlands. The study was undertaken concurrently with a British cohort for comparison and validation of the Dutch study. Methods The study enrolled and stratified 207 patients by AJCC stage. The conventional schedule group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Detailed methods of this multicentre, nonblinded, randomized clinical trial (ClinicalTrials.gov registration number: NCT01018004), initiated by the Department of Surgical Oncology at the University Medical Centre of Groningen (UMCG), have been described previously. [14][15][16] In summary, however, participants were randomized, in a 1:1 fashion, into 2 groups: one following the conventional schedule recommended in the current UK NICE or Dutch National melanoma guidelines, 17,18 and one whose follow-up was an AJCC stageadjusted reduced schedule (Table 1). Patients were stratified by country and AJCC stage (seventh edition), 19 in 2 random permuted blocks of 4 patients, generated by a validated system (Intrialgrator) with the use of a pseudorandom number generator and a supplied seed number.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed methods of this multicentre, nonblinded, randomized clinical trial (ClinicalTrials.gov registration number: NCT01018004), initiated by the Department of Surgical Oncology at the University Medical Centre of Groningen (UMCG), have been described previously. [14][15][16] In summary, however, participants were randomized, in a 1:1 fashion, into 2 groups: one following the conventional schedule recommended in the current UK NICE or Dutch National melanoma guidelines, 17,18 and one whose follow-up was an AJCC stageadjusted reduced schedule (Table 1). Patients were stratified by country and AJCC stage (seventh edition), 19 in 2 random permuted blocks of 4 patients, generated by a validated system (Intrialgrator) with the use of a pseudorandom number generator and a supplied seed number.…”
Section: Methodsmentioning
confidence: 99%
“…Previously published results of the interim analysis of both studies at 3 years demonstrated the highly correlated data between the 2 countries. 14,15 After 5 years of follow-up, 240 (61.9%) completed and returned the PROMs questionnaires. The overwhelming majority ( > 97%) of patients remained satisfied with their follow-up schedule, regardless of the frequency of clinic visits.…”
Section: Quality Of Life and Patient-reported Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients also incur travel and parking expenses, which may be especially burdensome for those who do not live close to the treatment centre. Fewer routinely scheduled clinic visits may have little impact on the detection of subsequent new primary or recurrent melanomas [12] and could result in substantial cost savings [13][14][15].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Optimal follow-up surveillance strategies for patients who have been treated for primary melanoma by wide excision with or without SN biopsy have not been determined and are somewhat controversial, 9 but there are ongoing attempts to assemble evidence indicating the costeffectiveness of various follow-up schedules, notably the MELFO studies. 10,11 Although longer follow-up of these studies is required, results to date have shown that a less intensive follow-up schedule, with fewer clinic visits and less frequent routine imaging tests, did not adversely affect outcomes and substantially reduced costs for both patients and healthcare systems. Until now, there has been no information about the efficacy and cost of various followup surveillance strategies for melanoma patients who have had a positive SN but not a CLND, as in the experimental arms of both the MSLT-II and DeCOG-SLT studies.…”
mentioning
confidence: 99%